Umar Bin Khatab's Leadership Policy Strategy In Pancasila Perspective - Iwan Sumiarsa; Muhamad Husein Maruapey; R. Oetje Subagdja (Journal La Bisecoman, 2024)
The thesis entitled Umar Bin Khatab's Leadership Policy Strategy in the Pancasila Perspective is with the aim of discussing how the policy strategy implemented by Umar Bin Khatab as one of the leading caliphs in Islamic history, was able to implement the principles of Pancasila in various steps and policies he took during his leadership. In this study, the method used is a qualitative research method, which is a research based on the philosophy of positivism, used to examine the natural condition of objects, where the researcher is the key instrument. Data collection techniques are carried out using a triangulation approach (combined), data analysis is inductive / qualitative, which emphasizes meaning rather than generalization. The expected result in this study is to be able to contribute to enriching leadership insights based on universal values in the context of Pancasila based on the historical context and development of the life of Indonesian society which is pluralism.